Administrative reform and regime shifts reflections on the Thai polity. - Bowornwathana, Bidhya (1994)
"Aucoin has identified two paradigms - public choice and managerialism - which are of relevance to administrative reform. These paradigms are outlined, along with a regime-survival paradigm which is suggested as a necessary additional means of understanding the dynamics of reform in unstable regimes. The latter paradigm in particular is then used to inform a discussion of selected areas of reform in the Thai polity during the Suchinda/Anand and Chuan administrations"
Keywords: Administrative agencies - Reorganization; Administrative reforms - Thailand